Relationship between nutritional adequacy and anthropometric profile characteristics according to playing position in professional female soccer players: a cross-sectional study - Kong-Lozano, L. A.; Leveau-Barrera, N.; Aquino, R.; Parada, N. E. C.; Galán, B. S. M. (BMC Sports Science, Medicine and Rehabilitation, 2026)
Background Anthropometric characterization and somatotype profiling in professional soccer players are essential for understanding the morphofunctional demands associated with playing positions.